ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT DENGAN DUE PROFESSIONAL CARE SEBAGAI VARIABEL MODERATING PADA KANTOR AKUNTAN PUBLIKDI MEDAN - Khairul Amri Hasibuan; Ade Fatma Lubis; Rina Bukit (Jurnal Mantik Penusa, 2018)
The purpose of this research was to analyze the influence independence, audit planning, audit supervision, accountability and integrity on audit quality simultaneously and partially and to find out that due professional care coulde moderate the correlation of independence, audit planning, audit supervision, accountability and integrity with audit quality on Accounting Firm in Medan. The research used causal assosiative research method. The population and samples consisted 71 auditor at Public Accountant Firm in Medan, taken by census method. The data gathered by using questionnaires and analyzed by using multiple regression analysis and residual test. The result of the research showed the independence, audit planning, audit supervision, accountability and integrity simultaneously had significant influence on audit quality. The partially, only independence, accountability and integrity which had positive and significant influence on audit quality, while audit planning had negative and insignificant and audit supervision had positive but insignificant influence on audit quality. The variable of due professional care could not moderatethe correlation of the variables of independence, audit planning, audit supervision, accountability and integrity with audit quality at the Accounting Firm in Medan